Identity Formation in Children and Young People in Open Adoptions from Out-of-home Care in New South Wales, Australia. Issue 2 (3rd April 2018) - Luu, Betty; de Rosnay, Marc; Wright, Amy Conley; Tregeagle, Susan
ABSTRACT: Semi-structured interviews were used to explore identity development for nine adoptees (aged 9–23 years) who were adopted by their foster carers in New South Wales, Australia. Adoptions were open, with court-ordered face-to-face contact with birth families. Findings suggest that participants had healthy adoptive identities, with coherent and meaningful narratives about their life histories. Adoption provided a sense of security and belonging. Openness provided information to build a self-narrative and encouraged discussion of adoption issues within adoptive families. Adoptive parents were critical in helping children understand their adoption and facilitating direct contact with birth families, thus laying foundations for positive identity development.